Accessible communication in the transport of non-urgent people with communication impairments. (24th June 2020) - Soares, EM; Granjo, T; Monteiro, S; Bemposta, S; Salvador, A
Abstract: Introduction Paramedics may find innumerous circumstances that require careful consideration of the patient's clinical condition. Because of that, communication between paramedics and patients in a critical condition must be as clear and effective as possible. Objectives This study aims to identify the communicative needs of ambulance's crew members when transporting non-urgent people with communicative impairments and to create a tool that facilitates the communicative process. Methodology A brainstorming was held at Associação de São Jorge to gather information regarding the needs and difficulties experienced by the ambulance's crew members. An audio record of this meeting was collected and a qualitative analysis was carried out. Additionally, a questionnaire was fulfilled. Based on these results, a first version of the communicative tool was developed. A pluridisciplinary focus group was held to discuss it, regarding content, form and utility. After this focus group, the second version of the communicative tool was elaborated to be tested by the crew members of this association. As so, a dynamic of three hours was implemented to empower these professionals to use this tool and other communicative strategies. Results The qualitative analysis of the first meeting collected data recognize as crew member's needs: communicating basic and immediate needs at clinical level and at colloquial discourse. This data allowed to establish parameters for the construction of the first version of the communicative tool. The referred focus group identified the need to improve it, considering: format, content and also the need to complement this tool with other communicative facilitators (e.g. braille; gestures). Conclusion This study shows the need of facilitating the communication in non-urgent transportation. Despite the modifications that have to be done, the communicative tool that was developed already shows a positive impact in the ambulance crew and in the community.